Will there be a shale gas revolution in China by 2020? - Gao, F (Oxford Institute for Energy Studies, 2012)
This paper, by Fan Gao, assesses the extent to which China is likely to achieve levels of shale gas production by 2020 which would make a meaningful difference to its growing need for imports of pipeline gas and LNG. The study suggests that given the rather disappointing progress on Coal Bed Methane production since exploration and development work started some 25 years ago, a cautionary approach is needed in anticipating the outlook for shale gas for the remainder of this decade. The specific challenges include water availability and population density demographics as well as the need to stimulate an innovative competitive dynamic in the Chinese upstream service sector and an appropriate upstream investment framework with foreign participants for the transfer and application of technology. The paper provides a rare appreciation of the dynamics of the onshore Chinese upstream industry and from that basis a better understanding of what will be required, on a number of policy levels, for Chinese shale gas development to succeed.